Integration of transcriptomic, proteomic and metabolomic data to reveal the biological mechanisms of AAI injury in renal epithelial cells. (February 2021) - Li, Yu; Xu, Houxi; Cai, Danhong; Zhu, Sirui; Liu, Xiaoli; Zhao, Ye; Zhang, Zhaofeng; Bian, Yaoyao; Xue, Mei; Zhang, Liang
Abstract: Overexposure to aristolochic acid I (AAI) can induce aristolochic acid nephropathy (AAN). However, the comprehensive mechanisms of AAI-induced nephrotoxicity have not been entirely explicated. To investigate the toxicological mechanisms by which AAI induces renal injury, human kidney cells (HK-2 cells) were subjected to comprehensive transcriptomic, proteomic and metabolomic analyses. The transcriptomic analysis identified a total of 7749 differentially expressed genes (DEGs) after AAI treatment, while the proteomic analysis found 598 differentially expressed proteins (DEPs) after AAI treatment. The metabolomic analysis revealed 49 and 42 differentially expressed metabolites (DEMs) in the positive and negative ion modes, respectively. Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed on these DEGs, DEPs and DEMs. The results of the comprehensive analyses of transcripts, proteins, and metabolites indicated that the DEGs, DEPs, and DEMs were jointly regulated in three ways. These genes, proteins and metabolites and their related dysregulated pathways may be promising targets for research on the mechanisms of AAI injury in human renal epithelial cells. This study provides large-scale omics data that can be used to formulate new strategies for the prevention, rapid diagnosis, and treatment of AAI injury. Highlights: AAI induced significant cytotoxicity in HK-2 cells. The integrative omics analysis demonstrated that AAI damage to HK-2 cells involves 3 pathways. Large-scale omics data illuminate the features of AAI poisoning.